PENGARUH BIAYA AUDIT, AUDIT TENURE DAN ROTASI KAP TERHADAP KUALITAS AUDIT - Hendi; -, shirley angelina (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The final result of this research is to identify the potential factors that can influenceand determine audit quality in Indonesia. It consists of Audit tenure, audit fees, andalso KAP rotation In this study, the sampling is from all sectors of the companiesthat have been existed and listed on the Indonesia Stock Exchange from the periodfrom 2016 to 2020, by using the purposive sampling method which requires thedisclosure of audit fee on an annual report for 5 years conservatively. The logisticregression method is applied in the process of testing the data. The final result showsthat there is a positive relationship between audit fees and audit tenure on auditquality, meanwhile, the KAP rotation shows a negative relationship on audit quality